Nonlinear MPC for a Sensorless Multi‐Vectored Propeller Airship Based on Sliding Mode Observer with Saturation. Issue 1 (6th August 2018) - Wen, Yubin; Chen, Li; Liang, Kuankuan; Duan, Dengping
Abstract: A nonlinear fault tolerant station keeping controller for a multi‐vectored propeller airship without velocity and angular velocity sensors is developed, which is composed of three modules: nonlinear model predictive controller (NMPC), sliding mode observer (SMO), and linear programming (LP) based control allocation. The kinematics and dynamics model of the airship are introduced. Based on the nonlinear model, with the assumption that the velocity and angular velocity sensors are damaged, a sliding mode observer is designed to estimate the velocity and angular velocity of the airship. To achieve good performance in the station keeping mission, an explicit nonlinear model predictive control is derived. A linear programming base control allocation method is proposed to solve both amplitude and rate constraint of the propulsion forces and deflection angles. Stability analysis is carried out to prove that the system can be stabilized in finite time. Simulation results for the station keeping control are illustrated to prove the effectiveness of the proposed method.